Looking Beyond The Fourth Industrial Revolution (4IR): Implications and Prospects for Nigerian Academics - Dunmade, Aderinola Ololade; Ajani, Yusuf Ayodeji Yusuf; Yusuf, Suleiman; Ahmed, Abdulganiy Okanla (Edulib, 2023)
The Fourth Industrial Revolution (4IR) has brought about significant changes in various aspects of society, including education. This study aims to explore the implications and prospects of the 4IR for Nigerian academics. A qualitative research approach was used, and an online open-ended survey was conducted to gather data from Nigerian academics on their perceptions of the 4IR, the specific skills and knowledge areas they deemed important to succeed in the 4IR era, and their preparedness in these areas. The survey also aimed to explore the perceived opportunities and challenges of the 4IR for Nigerian academics and the role that higher education institutions could play in preparing them for the 4IR era. The data collected from the survey were analyzed thematically, and the study provided insights and conclusions that contributed to the existing literature on the implications and prospects of the 4IR for Nigerian academics. The results indicate that Nigerian academics perceive the 4IR as a significant opportunity, but they also recognize the challenges it presents. Participants identified several skills and knowledge areas as crucial for success in the 4IR era, including data analytics, critical thinking, and problem-solving. However, the study found that Nigerian academics feel inadequately prepared in these areas. The study highlights the need for higher education institutions to play a more significant role in preparing Nigerian academics for the 4IR era by developing new curricula, providing training opportunities, and creating partnerships with industry stakeholders. The findings of this study could inform policies and practices aimed at preparing Nigerian academics for the 4IR era, which could ultimately enhance Nigeria's economic growth and competitiveness in the global market. The study adhered to ethical considerations and institutional policies on research ethics.